2021
DOI: 10.3389/fphar.2021.691700
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Morphine Dependence and Withdrawal on the Reinforcing Effectiveness of Fentanyl, Cocaine, and Methamphetamine in Rats

Abstract: Recent estimates suggest increased popularity of the concurrent use of opioids and stimulants, with over 50% of treatment-seeking opioid users reporting regular stimulant use. The goal of the current study was to determine how opioid dependence and withdrawal affect the reinforcing effects of fentanyl, cocaine, and methamphetamine. Male Sprague-Dawley rats were allowed to self-administer fentanyl under a progressive ratio (PR) schedule of reinforcement. Baseline evaluations of reinforcing effectiveness of fent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The lack of 22-kHz USVs is consistent with the idea that somatic withdrawal symptoms are not driving craving behavior. Although rats may experience withdrawal-like behavior in early abstinence following chronic opioid self-administration ( Gipson et al, 2021 ; Seaman and Collins, 2021 ), withdrawal symptoms subside within the first few days of abstinence ( Welsch et al, 2020 ). Yet, craving continues to intensify for several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of 22-kHz USVs is consistent with the idea that somatic withdrawal symptoms are not driving craving behavior. Although rats may experience withdrawal-like behavior in early abstinence following chronic opioid self-administration ( Gipson et al, 2021 ; Seaman and Collins, 2021 ), withdrawal symptoms subside within the first few days of abstinence ( Welsch et al, 2020 ). Yet, craving continues to intensify for several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the current study, we examined fentanyl self-administration across a broad range of fentanyl doses (0.25, 0.75, 1.5, and 3.0 µg/kg/infusion) and hypothesized that relapse vulnerability would be highest following high-dose fentanyl self-administration. We also expanded our model to include an additional key feature of OUD in humans, physical dependence ( American Psychiatric Association, 2013 ), as assessed by spontaneous weight loss during early withdrawal, a highly predictive single factor of withdrawal ( Cicero and Meyer, 1973 ; Gellert and Holtzman, 1978 ; Nickel and Aledter, 1987 ; Maldonado et al, 1992 ; Houshyar et al, 2004 ; Navarro-Zaragoza et al, 2010 ; Pintér-Kübler et al, 2013 ; Bobzean et al, 2019 ; Seaman and Collins, 2021 ; Townsend et al, 2021 ). Physical dependence is a defining feature of OUD in humans ( American Psychiatric Association, 2013 ), and women experience a more severe withdrawal syndrome than men ( Huhn and Dunn 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies lay the groundwork for a deeper evaluation of the interactions between the reinforcing effects of methamphetamine and fentanyl using drug-vs.-drug choice. For instance, previous studies from our laboratory and others have demonstrated that the reinforcing effects of opioids, but not stimulants, are enhanced when subjects are in a state of opioid withdrawal (47,55,56). However, the degree to which opioid withdrawal would impact preference for and/or economic interactions between methamphetamine and fentanyl is an important and underexplored aspect of the current epidemic of polysubstance use.…”
Section: Discussionmentioning
confidence: 97%
“…Rats were anesthetized with 2–3% isoflurane and prepared with chronic indwelling catheters in the left and right femoral veins using procedures similar to those described previously ( 37 , 47 , 48 ). Catheters were tunneled under the skin and attached to a vascular access button placed in the mid-scapular region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation